Power quality improvement using dynamic voltage restorer in electrical distribution system: an overview - Ali Basim Mohammed; Mohd Aifaa Mohd Ariff; Sofia Najwa Ramli (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper represents a review of the dynamic voltage restorer for power quality improvement in the electrical distribution system. Over the past 50 years, issues concerning power quality have steadily increased, to prevent the effect of the voltage disturbances, some of the devices are put as a solution to these problems such as distribution static compensator (D- STATCOM), solid-state transformer (SST), uninterruptible power supply (UPS), dynamic voltage restorer (DVR). The DVR is one of the economic solutions to overcome the voltage disturbances like voltage sag/swell and harmonics. It is widely used to mitigate the voltage disturbances in the power distribution system, especially in the medium and low distribution networks. This paper aims to review the implementation of the DVR in the system integrated with renewable energy resources. This is important because the future of electricity business is moving towards renewable energy and also provides a thorough discussion of the typical components, controllers, compensation methods, and the application of DVR. The extensive review of the technology aims to ease and speed up the development and the advancement of the DVR in the near future.